Amelioration of a highly degraded tropical alfisol by planting 1. Changes in soil physical and chemical properties - Hulugalle, N.R. (1992)
This paper examines soil amelioration by planting 15 leguminous and graminaceous plant species, including herbaceous annuals, perennials and biennials, and woody perennials and biennials. Disturbed and undisturbed natural regrowth were planted with leguminous species, in some cases with fertilizer applied at planting (400 kg ha- of 15: 15: 15 NPK). The studies were made on two highly degraded sites in southwestern Nigeria which had been subjected to intensive mechanized cropping for a period of 10 years. Changes in soil physical and chemical properties were monitored from 1989 to 1991. Acacia dificilis, Brachiaria lata and Mucuna utilis had the lowest survival rates by the following growing season. Soil fertility and compaction levels differed between sites. Planting had no effect on the latter. The decreases in compaction (i.e. macroporosity) between 0.00 and 0.10 m depth at both sites one month before and five and 17 months after planting were 43, 59 and 61 per cent, respectively were attributed to exclusion of heavy machinery from the sites. Large decreases in fertility occurred at both sites and were attributed to a combination of nutrient extraction and to leaching. Between fallow species, exchangeable Ca, pH and the cation-exchange capacity (CEC) were greater and total acids lower for herbaceous cover compared with woody perennials, and was attributed to a higher Ca demand by the latter. Highest and lowest values of Ca, CEC and pH occurred in plots where plant material was returned to the soil (i.e. by cutting or die-back) and in cropped plots, respectively. Natural regrowth was as effective or better than planted species in improving soil physical and chemical properties. Therefore the use of exotic plant species for ameliorating highly degraded alfisols is unnecessary. Amelioration of highly degraded alfisols may be best effected by allowing natural regrowth t.0 occur while excluding all mechanized traffic from the site.